Think-Pair-Share: Can It Improve Students' Writing Skills? - Edi Prasetiyo, I Komang; Krismayani, Ni Wayan; Agung Gana Kumara, Dewa Gede (Journal on Studies in English Language Teaching (JOSELT), 2025)
Proficiency in writing involves not only understanding linguistic elements but also being able to process language and information in real-time. Preliminary research showed that most VIII G students at SMPN 4 Sukawati needed help with writing, particularly paragraph organization. To accomplish the goal, the researchers carried out two cycles of classroom action research. Tests, questionnaires, and research tools were used to gather the necessary data. Comparing the pre-test and post-test findings allowed for data analysis and revealed that the subjects' mean scores had significantly improved from the pre-test to the post-test. The questionnaire findings, also given out after the last cycle, provided evidence that the use of think pair share was well received. It may be inferred from the study instruments' results that think-pair-share can help SMPN 4 Mengwi seventh-grade students' writing abilities.